interdisciplinary research in sciences: University National Santiago Antúnez de Mayolo 2009 - 2017 - Yslado, Rosario (2019)
The general objective of the study was to analyze the characteristics of the interdisciplinary research carried out at the National University Santiago Antúnez de Mayolo (UNASAM), pe-riod 2009 - 2017. The specific objectives were: a) to describe the sociodemographic charac-teristics of the interdisciplinary researchers of UNASAM; b) determine the general character-istics of the interdisciplinary research carried out at UNASAM; c) analyze the conceptual - theoretical characteristics of the interdisciplinary research carried out atUNASAMand d) analyze the methodological characteristics of the interdisciplinary research carried out at UNASAM. The study was descriptive and transversal. The sample consisted of 92 research reports completed and financed. The documentary analysis technique was used, with an ad hoc instrument of 37 items, with content validity (Pc = 0, 04). The main results were: re-search carried out in Huaraz (69, 6 %); without incorporating external collaborators (82, 6 %) or internal collaborators (93, 5 %). 71, 7 % have not been published. 54, 5 % of the studies meet the theoretical-conceptual characteristics of interdisciplinary research. Regarding the technicalmethodological characteristics, most are quantitative (96, 7 %), applied (82, 6 %), de-scriptive (58, 7 %), non-experimental (56, 5 %), non-probabilistic (68, 5 %); with observation and survey techniques (59,6 %), they preferably used the questionnaire (28, 8 %); in 62, 0 % they used methods of descriptive statistics. In the analytic-inferential, the results obtainedwere coherent with the proposed objectives (56,5 %), the discussion (57, 6 %), and the conclu-sions (78, 3 %) integrated contributions from various scientic disciplines. The conclusion of the study indicates that most of the plinary research analyzed meet the characteris-tics theoretical-conceptual, technical-methodological and analytical-inferential, concordant with interdisciplinary practice